Birth, death, and femininity : philosophies of embodiment - Schott, Robin May; Heinämaa, Sara, 1960- (Book collections on Project MUSE., 2010)
Issues surrounding birth and death have been fundamental for Western philosophy as well as for individual existence. The contributors to this volume unravel the gendered aspects of the classical philosophical discourses on death, bringing in discussions about birth, creativity, and the entire chain of human activity. By linking their work to major thinkers such as Heidegger, Nietzsche, Beauvoir, and Arendt, and to major philosophical currents such as ancient philosophy, existentialism, phenomenology, and.